Premelting anomalies in pyromellitic dianhydride: negative thermal expansion, accelerated radiation damage, and polymorphic phase transition - Poręba, Tomasz; Świa̧tkowski, Marcin; Ernst, Michelle; Confalonieri, Giorgia (The journal of physical chemistry. C, Energy, materials, and catalysis, 2022)
We have established a comprehensive approach to evaluate the structure-property relationships in solid pyromellitic dianhydride (PMDA) at high temperature. Synchrotron single-crystal X-ray diffraction experiments have yielded structural models for this volatile compound up to 250 °C. PMDA exhibits negative thermal expansion around 145 °C, which is correlated to geometrical changes in the intermolecular carbonyl-carbonyl interactions. A reversible phase transition above ca. 210 °C was detected by differential scanning calorimetry and is associated with the lowering of the molecular symmetry, as indicated by Raman spectroscopy. X-ray powder and single-crystal diffraction data confirm the formation of a new high-temperature monoclinic phase, with two symmetry-independent anhydride groups in the asymmetric unit. The influence of pyromellitic acid impurities on the formation temperature of the new phase has been investigated, and thermodynamic parameters of pure pyromellitic dianhydride have been revaluated. Additionally, the analysis of the temperature- and time-dependent variations in the diffraction patterns allowed us to track the augmented radiation-driven decarboxylation upon heating. Significantly, the formation of a high-temperature low-symmetry phase in PMDA may challenge the solid-state polymerization that aims for highly oriented materials.
Gesehen am 24.08.2022